Монголын нутгийн удирдлагын загвар, түүний төлөвшил дэх улс төрийн асуудал - Ё.Довчин; Ц.Батболд (Politology, 2023)
Political parties system of municipalities unfit for limited participation. lt explained agrument of science foundation. That unfit participation, which is impact indicative and why citizenry are sleepy participation to no purpose. That all upwardly of conclution for shirttail meaning.